BIODIESEL FROM AVOCADO SEEDS BY TRANSESTERIFICATION PROCESS - Risnoyatiningsih, Sri (Jurnal Teknik Kimia, 2010)
The existence of Biodiesel as an alternative fuel from year to year has decreased quantity and will become lessand less because of rising demand. One source of biodiesel raw materials are seeds Avocadot.Seeds Avocadois still not utilized for other products, and avocado seeds contain fatty acid methyl esters of 71.715% asmaterial for biodiesel. The aim of this research is to make biodiesel from avocado seed oil so it can be used asalternative diesel fuels and also take advantage of avocado seed in order to have a high value in order to beprocessed into biodiesel. Operating conditions used was 10 ml volume of oil, transesterification temperature ±60 ° C, NaOH to oil weight ratio of 1% and stirring speed 600rpm. Also, studies conducted on the oil to methanolmole ratio 1:4, 1:6, 1:8, 1:10, 1:12 and with a variation of 5, 20, 35, 50 and 65 minutes. Peneliatianresults show that biodiesel meets the standard avocado seed oil as an alternative fuel in Indonesia because ithas a value of flash point between 130 ° C to 240 ° C and has a pour point value between -2 ° C to 9 ° C.Keywords: Seeds of avocado, transesterification, biodiesel.